Uji selektivitas ekstrak etil asetat (EtOAc) biji putat air (Barringtonia racemosa) terhadap keong mas (Pomacea canaliculata) dan ikan lele lokal (Clarias batrachus) - Musri Musman; Sofyatuddin Karina; Kavinta Melanie (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. This study examined the selectivity of ethyl acetate extract of putat air (Barringtonia racemosa) in controlling Pomacea canaliculata compared to local catfish (Clarias batrachus). Five concentration of putat air (25, 50, 100, 200, and 400 ppm) with triplicate were tested in this study. The powder of putat air kernel was extracted through increasing the polarity of solvent, i.e. dichloromethane, ethyl acetate, and methanol. The mortality data were analyzed using Trimmed Spearman Karber (TSK) program version 1.5. The selectivity value was calculated based on LC50 values obtained from TSK. The results showed that (1) LC50 values of putat air's kernel extract of putat air to P. canaliculata and C. batrachus were 25.00 and 87.06 ppm, respectively, (2) the selectivity value of putat air's kernel extract as molluscicide of P. canaliculata was 3.48. Key words: Pomacea canaliculata, local catfish (Clarias batrachus), putat air (Barringtonia racemosa).